2016
DOI: 10.1038/srep20036
|View full text |Cite
|
Sign up to set email alerts
|

Dietary soy and meat proteins induce distinct physiological and gene expression changes in rats

Abstract: This study reports on a comprehensive comparison of the effects of soy and meat proteins given at the recommended level on physiological markers of metabolic syndrome and the hepatic transcriptome. Male rats were fed semi-synthetic diets for 1 wk that differed only regarding protein source, with casein serving as reference. Body weight gain and adipose tissue mass were significantly reduced by soy but not meat proteins. The insulin resistance index was improved by soy, and to a lesser extent by meat proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 57 publications
(67 reference statements)
4
48
1
Order By: Relevance
“…Furthermore, the growth rate of mice fed different protein diets tended to be slow, and even decreased over the feeding period. The growth rates were different from previous studies using a rat model (43), which may be related to the physiological performance of the animals themselves and the time of dietary intervention.…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, the growth rate of mice fed different protein diets tended to be slow, and even decreased over the feeding period. The growth rates were different from previous studies using a rat model (43), which may be related to the physiological performance of the animals themselves and the time of dietary intervention.…”
Section: Discussioncontrasting
confidence: 96%
“…This indicated that SPI inhibited the feed conversion rate. Similar results were observed in previous studies [23,26], in which growing rats were fed casein or SPI AIN-93G diets. In those studies, however, the decline in feed conversion efficiency in the SPI rats was not caused by the increased feed intake, but by the decreased weight gain.…”
Section: Discussionsupporting
confidence: 91%
“…In animal studies, dietary meat proteins have been shown to affect gut microbiota, metabolism in liver, and host health (18, 19). The quality of dietary meat proteins is quite important.…”
Section: Discussionmentioning
confidence: 99%